Rheo-mechanics, durability and microstructural characterisation of slag-nodified metakaolin-based geopolymer concrete for extrusion-based 3D printing applications - Jaji, Mustapha Bamidele (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.